PERBANDINGAN PENGUNGKAPAN KALA DALAM BAHASA JEPANG DAN BAHASA INDONESIA - Elizabeth Ika Hesti Aprilia Nindia Rini (Diponegoro University, 2018)
(Contrastive study between tenses in Japanese and Indonesian Languages) Expressing time in sentences is universal in any language, although it's marked differently in each language. This research objective is to know the differences in tenses marker between Japanese and Indonesian languages. The method used is the descriptive method. As a result of the research findings, it was found that in the Japanese language tenses are marked by morphemic forms were characterized by bound morphemes, whereas Indonesian tenses are marked as lexical by the adverb. Attendance adjunct in Japanese is optional, in Indonesian adjunct explain the position, activity, state of theft with the time of speech.Keywords: tense, bentuk -ru, bentuk -ta, adverbia kala